Benchmark of Density Functionals for the Calculation of the Redox Potential of Fe3+/Fe2+ Within Protein Coordination Shells - Listyarini, Risnita Vicky; Gesto, Diana Sofia; Paiva, Pedro; Ramos, Maria João; Fernandes, Pedro Alexandrino (Frontiers in Chemistry, 2019)
Iron is a very important transition metal often found in proteins. In enzymes specifically, it is often found at the core of reaction mechanisms, participating in the reaction cycle, more often than not in oxidation/reduction reactions, where it cycles between its most common Fe(III)/Fe(II) oxidation states. QM and QM/MM computational methods that study these catalytic reaction mechanisms mostly use density functional theory to describe the chemical transformations. Unfortunately, density functionals is known to be plagued by system-specific and property-specific inaccuracies that cast a shadow of uncertainty over the results. Here we have modelled 12 iron coordination complexes, using ligands that represent amino acid sidechains, and calculated the accuracy with which the most common density functionals reproduce the redox properties of the iron complexes (specifically the electronic component of the redox potential at 0 K, 〖"∆E" 〗_"elec" ^(〖"Fe" 〗^"3+" "/" 〖"Fe" 〗^"2+" )), using the same property calculated with CCSD(T)/CBS as reference for the evaluation. A number of hybrid and hybrid-meta density functionals, generally with large % of HF exchange (such as BB1K, mPWB1K and mPW1B95) provided systematically accurate values for 〖"∆E" 〗_"elec" ^(〖"Fe" 〗^"3+" "/" 〖"Fe" 〗^"2+" ), with MUEs of ~2 kcal/mol. The very popular B3LYP density functional was found to be quite precise as well, with a MUE of 2.51 kcal/mol. Overall, the study provides guidelines to estimate the inaccuracies coming from the density functionals in the study of enzyme reaction mechanisms that involve an iron cofactor, and to choose appropriate density functionals for the study of the same reactions.